John Paul II’s contribution to development of the Apostleship of the Sea - Edward Pracz (Polonia Sacra, 2014)
The point of this article was to present the continuity of John Paul II’s teaching with the teaching of his predecessors and, at the same time, what was novelty and contribution in the care of the Apostleship of the Sea. The contribution included organization of structures and essential documents to which those responsible for the Apostleship of the Sea may refer.